Effect of thermocycling on the color stability of different shades of composite resins - Okida, Ricardo Coelho [UNESP] (2013)
The aim of this study was to evaluate the effect of thermocycling on color alterations of three different composite resins. The factors in study were Enamel Composite Resin at three levels (Esthetic X, Opallis e Vênus); Dentine Composite Resin at three levels (Esthetic X, Opallis e Vênus) and thermocycling at one level (3000 cycles). The response variable was of color altering measured through spectophotometry. For that matter, 60 specimens were made, divided in six groups for study: GI - Esthetic X (Enamel); GII - Esthetic X (Dentine); GIII - Opallis (Enamel); GIV - Opallis (Dentine); GV - Venus (Enamel); GVI - Venus (Dentine). All the specimens were made using a mold in order to standardize the sample size. The inserts of the composites were made by increments and cured through a halogenous light Ultralux device (Dabi Atlante, Ribeirão Preto, Brazil) with potency of 450mW/cm2. After the confection, all specimens were subjected to chromatic analysis on a Visible Ultraviolet Reflection Spectrophotometer, model UV- 2450 (Shimadzu, Kyoto, Japan), with color alterations calculated through the CIE L*a*b* system. Next, they were stored in isolated containers filled with artificial saliva at 35oC ± 2°C, during three months. Then, they were subjected to thermocycling effects of 3000 cycles of thermal variation of 5oC to 55oC. Right after, the specimens were subjected once more to chromatic analysis. An ANOVA statistical test at 5% was applied for analysis of the results for both factors of the color alterations of the tested composite resins. The results showed a statistical equality between the enamel composite resins Esthetic X and Venus (p = 0,79); the same wasn't observed between Esthetic X and Opallis enamel composite resins, where color alterations were statistically higher for the Opallis composite (p = 0,0000002). The same ocurred between Opallis and Venus enamel composite resins, where again Opallis showed a higher statistical average of color alteraion (p = 0,0000005). As for the dentine composite resins, all three composite resins showed a statistical equality. It is concluded that all of the studied composite resins suffered color alterations and the Opallis enamel composite resin suffered most color alterations after thermocycling. © Nova Science Publishers, Inc.